THE ROLES OF HEDGEHOG AND AP-2 SIGNALING IN THE REGULATION OF LENS DEVELOPMENT - Kerr, Christine L. (My University, 2014)
Lens development is an intricate process governed by growth factor signaling and a hierarchy of transcription factors that regulate important processes required for normal lens development.
Midline hedgehog (Hh) signaling has been implicated in lens defects including cyclopia and lens degeneration in rodents and fish. A lens specific model of hedgehog signaling has not been examined, and it was unknown whether the lens is able to respond to Hh signals. To investigate this question, and to determine any consequences of abnormal Hh signaling on lens development, a mouse model of constitutively active smoothened in the surface ectoderm and derivatives, (including the lens), was created. These mutants exhibited ectopic expression of FoxE3 by E12.5, and ectopic Pax6 expression by E15.5, along with deregulation of the lens cell cycle and lens degeneration.
Similar to the Hh signaling pathway, normal expression of the transcription factor Activating Protein-2 (AP-2, tcfap2), in the lens, was shown to be essential for the maintenance of an epithelial cell phenotype, and the regulation of the lens cell cycle. AP-2α has been shown to be important at the placode stage of development for correct separation of the lens vesicle away from the overlying surface ectoderm. Defects resulting from the loss of AP-2α at this stage do not manifest until E12.5, at time at which AP-2β expression is lost in the lens, suggesting possible redundancy between the two AP-2 family members in early lens development.
To investigate this possible redundancy, Tcfap2a and Tcfap2b were conditionally deleted from the lens at E9.5 (AP-2α/β DKOs). These family members were shown to play redundant roles during early lens development, with the double mutants exhibiting more severe defects than those seen in the AP-2α single knockout model A more nasally positioned lens stalk and a rotated lens were observed. Severe corneal defects and deregulation of the lens cell cycle were also evident.
Roles for AP-2α in later lens development were unknown. To examine whether or not this transcription factor continues to play a role in lens epithelial cell maintenance subsequent to lens vesicle separation, a mouse model with Tcfap2a conditionally deleted from the lens during these later stages of development was created (MRL10-AP-2α). These mutants displayed a disorganized and multilayered lens epithelial cell layer with elongated epithelial cells that abnormally expressed fiber cell specific β/γ crystallins. These mutants also exhibited defects in cell adhesion between the epithelium and fiber cells, as well as between the epithelium and capsule, and exhibited fiber cell defects including vacuoles.
Together, the work presented in this thesis outline previously unknown roles for Hh and AP-2 signaling in lens development. Both Hh and AP-2 are required for the maintenance of a normal lens epithelial cell phenotype and regulation of the cell cycle. This thesis also illustrates the requirement (and redundant roles) for AP-2α and AP-2β at the lens placode stage of development.
Keywords: Development; Transcription Factors; AP-2alpha; Hedgehog Signaling; Genetics; AP-2beta; Biology; Developmental Biology; Genetics; Biology